Efficient and Stable Inverted Perovskite Solar Modules Enabled by Solid–Liquid Two-Step Film Formation - Zhang, Juan; Ji, Xiaofei; Wang, Xiaoting; Zhang, Liujiang; Bi, Leyu; Su, Zhenhuang; Gao, Xingyu; Zhang, Wenjun; Shi, Lei; Guan, Guoqing; Abudula, Abuliti; Hao, Xiaogang; et al. (Nano-Micro Letters, 2024)
A considerable efficiency gap exists between large-area perovskite solar modules and small-area perovskite solar cells. The control of forming uniform and large-area film and perovskite crystallization is still the main obstacle restricting the efficiency of PSMs. In this work, we adopted a solid–liquid two-step film formation technique, which involved the evaporation of a lead iodide film and blade coating of an organic ammonium halide solution to prepare perovskite films. This method possesses the advantages of integrating vapor deposition and solution methods, which could apply to substrates with different roughness and avoid using toxic solvents to achieve a more uniform, large-area perovskite film. Furthermore, modification of the NiOx/perovskite buried interface and introduction of Urea additives were utilized to reduce interface recombination and regulate perovskite crystallization. As a result, a large-area perovskite film possessing larger grains, fewer pinholes, and reduced defects could be achieved. The inverted PSM with an active area of 61.56 cm2 (10 × 10 cm2 substrate) achieved a champion power conversion efficiency of 20.56% and significantly improved stability. This method suggests an innovative approach to resolving the uniformity issue associated with large-area film fabrication. Highlights: 1 High-quality large-area perovskite films are prepared using a solid–liquid two-step film formation method combined with CsBr modification for the buried interface and Urea additive for perovskite crystallization. 2 The inverted perovskite solar modules’ performance is enhanced to 20.56% in 61.56 cm2 with improved stability.